PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DALAM PEMBELAJARAN B. INDONESIA UPTD SD NEGERI 125138 PEMATANGSIANTAR - Simanjuntak, Melvin; Ruth Nur Sanna Hutahaean (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of using the game based learning (wordwall) learning model on the learning outcomes of B. Indonesia class IV students. The research uses a quantitative type of research with the research method used in this research being a quasi-experimental method (Quasi Experimental). An experiment is a form of design that involves two groups where one group is the experimental group and the other group is the control group. The research population was class IV students at Pematangsiantar State UPTDSD, with a sample of all class IV A (experimental class) of 17 students and class IV B (control class) of 19 students. Data was collected using tests, hypothesis testing was carried out using independent samples t-test on samples showing a significance value of 000 <0.05 with a mean post test value for the control class of 50.00 and the experimental class of 74.41. These results prove that there is a positive influence of using the game based learning (wordwall) learning model on improving students' B.Indonesia learning outcomes.